Hypoxia-activated pro-drug TH-302 exhibits potent tumor suppressive activity and cooperates with chemotherapy against osteosarcoma. Issue 1 (1st February 2015) - Liapis, Vasilios; Labrinidis, Agatha; Zinonos, Irene; Hay, Shelley; Ponomarev, Vladimir; Panagopoulos, Vasilios; DeNichilo, Mark; Ingman, Wendy; Atkins, Gerald J.; Findlay, David M.; Zannettino, Andrew C.W.; Evdokiou, Andreas
Highlights: TH-302 is a promising hypoxia activated pro-drug (HAP) with demonstrated anticancer efficacy against solid and haematological malignancies. Osteosarcoma (OS) is the most frequent primary malignancy of bone. Bone is intrinsically hypoxic thus making OShighly susceptible to HAPs. TH-302 induces hypoxia-dependent cytotoxicity to human OS cell lines but exerts limited or no toxicity to normal human osteoblasts. TH-302 reduces tumour burden in bone, cooperates with doxorubicin against OS-induced bone destruction and limits pulmonary metastases. Importantly, we have shown for the first time that TH-302 treatment has no effect on normal bone metabolism as assessed by high resolution micro CT. Abstract: Tumor hypoxia is a major cause of treatment failure for a variety of malignancies. However, tumor hypoxia also offers treatment opportunities, exemplified by the development compounds that target hypoxic regions within tumors. TH-302 is a pro-drug created by the conjugation of 2-nitroimidazole to bromo-isophosphoramide (Br-IPM). When TH-302 is delivered to regions of hypoxia, Br-IPM, the DNA cross linking toxin, is released. In this study we assessed the cytotoxic activity of TH-302 against osteosarcoma cells in vitro and evaluated its anticancer efficacy as a single agent, and in combination with doxorubicin, in an orthotopic mouse model of human osteosarcoma (OS). In vitro, TH-302 was potently cytotoxic to osteosarcoma cells selectively under hypoxic conditions, whereas primary normal human osteoblasts were protected. Animals transplanted with OS cells directly into their tibiae and left untreated developed mixed osteolytic/osteosclerotic bone lesions and subsequently developed lung metastases. TH-302 reduced tumor burden in bone and cooperated with doxorubicin to protect bone from osteosarcoma induced bone destruction, while it also reduced lung metastases. TH-302 may therefore be an attractive therapeutic agent with strong activity as a single agent and in combination with chemotherapy against OS.